Architectural Conditions of A Jakarta State Vocational School: A Child-friendly School Design Perspective - Utami, Ailsa Raihanah; Barliana, Mokhamad Syaom; Mardiana, Riskha (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2023)
This research aims to explain the design principles of child-friendly vocational schools, describe the architectural conditions of the facilities and infrastructure in Jakarta 1 State Vocational School, and explain their suitability based on the design principles of child-friendly vocational schools. This research uses a qualitative approach with a descriptive method. Data collection techniques in this research use observation and documentation. The object of this research is the facilities and infrastructure of Jakarta 1 State Vocational School in the scope of a general learning room, a supporting learning room, and a specific learning room for construction and property engineering expertise. The final result explains that the architectural conditions of the facilities and infrastructure in Jakarta 1 State Vocational School are very suitable following the design principles of a child-friendly vocational school, including safety, health, comfort, easiness, and security requirements. The final suitability score is 74.5%. The most suitable assessment is on the Safety criteria, while the lowest is on the Comfort criteria.